A STUDY ON THE TECHNIQUES OF TEACHING READING TO THE FIRST YEAR STUDENT OF SMP NEGERI 2 COLOMADU - Utami , Sri (2011)
This research aims at describing the technique used by the teacher in teaching reading at the first year of SMP Negeri 2 Colomadu, knowing the problems faced by the teacher and the strategies implemented by the teacher to overcome the problems. This research is a descriptive qualitative research. The researcher collects the data by observing the English class and conducting in interview with the teacher. The data include syllabus, reading materials, field notes and interview script. And the methods of collecting the data are observation, interview, and documents. From the data analysis of the research finding and discussion, the researcher draws the conclusion. The first, the technique used by the teacher in teaching reading at the first year students of SMP Negeri 2 Colomadu is ICARE. It is an instructional model abbreviated from introduction, connection, apllication, reflection, and evaluation. The second, the problems faced by the teacher are; (1) the teacher finds difficulties in managing the class, (2) Each students has different capability in receiving the material, (3) the students have less confidence, (4) the teacher has limited time, the strategies to overcome the problems are; (1) the teacher walked around the class in order that the students listened to the explanation seriously, (2) the teacher should explain the material until the students understand, (3) the teacher asked one by one to answer the question, and the last (4) the teacher gives additional time or extra time to change the time which is expelled.